Pioneers of Spanish audiovisual infotaintment: Visual culture and satirical caricatures in "The Motin" - Valhondo-Crego, José Luis (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
In the late nineteenth century, the Spanish satirical press adopted a series of rhetorical strategies to offer the people a unique place within the representation of society. As Martínez Gallego has pointed out, the satirical weekly El Motín depicts an example of populist reason in the sense that Ernesto Laclau could argue. Through the content analysis of several cartoons, we examined the place that El Motín reserved to the floating signifier of the people. The satirical press let an illiterate working class deal with the issues of the political sphere.